Asymptomatic Primary Tumor Resection in Metastatic Colorectal Cancer: A Systematic Review and Meta-Analysis - Shu, Yefei; Xu, Ling; Yang, Wei; Xu, Xiaofeng; Zheng, Song (Frontiers in Oncology, 2022)
Background In patients with metastatic colorectal cancer (mCRC) with an asymptomatic primary tumor, there is no consensus on the indication for resection of the primary tumor. Methods The PubMed, Embase and the Cochrane Library databases were searched from inception to November 30,2021. A meta-analysis was performed using RevMan (version 5.3.3; The Cochrane Collaboration) on the outcome of mCRC patients with or without resection of the primary tumor in 8 selected studies. Results This meta-analysis included 2805 colorectal cancer patients with an asymptomatic primary tumor from 8 selected studies. Primary tumor resection (PTR) patients had longer overall survival (OS: MD =6.76 [3.39, 10.12], I2 = 77%, P < 0.0001), compared with non-primary tumor resection (NPTR) patients. In the subgroup, the randomized controlled trials (RCT) PTR group didn’t have longer overall survival (OS: MD =3.79 [-3.49, 11.08], I2 = 69%, P= 0.31); the Non-RCT PTR group had longer overall survival (OS: MD =8.42 [3.14, 13.70], I2 = 89%, P= 0.002). In the meanwhile, compared with NPTR group, the 2-year overall survival rate, the 3-year overall survival rate, 5-year overall survival rate in the PTR group is higher (OR=2.35 [1.74, 3.18], I2 = 0%, P < 0.00001; OR=3.61 [2.35, 5.54], I2 = 0%, P < 0.00001; OR=3.02 [1.72, 5.33], I2 = 48%, P= 0.0001, respectively). Conclusions Our results from studies demonstrate that the resection of primary tumor is a prognostic factor for survival in mCRC patients. However, 2 RCTs showed the resection of primary tumor was not related with a significant survival benefit in subgroup. Therefore, a larger RCT in the era of modern chemotherapy and liver resection techniques would be helpful.